Digital Comic Teaching Materials in Strengthening Character Education to Prevent Bullying Behavior for High School Students - Kusumawati, Niluh Ari; Djono; Rejekiningsih, Triana (Indonesian Values and Character Education Journal, 2024)
This study identifies the issue of the high prevalence of bullying behavior occurring in various environments, including social media, schools, communities, text messages, and homes. The study aims to analyze the effectiveness of digital comic teaching materials in strengthening character education to prevent bullying behavior among students. The method used in this study is a quasi-experimental design with a non-equivalent control group design (pretest-posttest). The subjects of the study involved 256 tenth-grade students and 6 guidance counselors. Data collection was conducted through questionnaires and observations related to students' experiences in witnessing bullying behavior. Data analysis utilized the N Gain test to measure the changes in outcomes before and after the intervention. The results show that digital comic teaching materials are effective in enhancing students' understanding of the importance of character education to prevent bullying behavior, with an average N Gain value of 91.04% in the experimental group. Based on these results, it can be concluded that digital comic teaching materials play a significant role in reducing bullying behavior and raising awareness of character education values among students.